Applying StarCS RNMPC with Real-Time Optimiser to Pilanesberg Platinum Mines Primary UG2 Milling Circuit. Issue 20 (2016) - Coetzee, L.C.; Ramonotsi, M.
Abstract: The StarCS RNMPC was recently updated by adding a real-time optimizer (RTO) to it. The enhanced controller was demonstrated on an industrial plant and the performance compared to the previous generation, which was already present. The results show that the RTO improved performance and stability of the process, as well as increased run-time, by eliminating short switch offs by the operators for manual intervention.